U2 L8 Chain and Quotient Rule CHAIN & QUOTIENT RULE

Slides:



Advertisements
Similar presentations
Chapter 11 Differentiation.
Advertisements

3.7 Implicit Differentiation
Linear Approximation and Differentials
Unit 6 – Fundamentals of Calculus Section 6
The Chain Rule Section 3.6c.
11.3:Derivatives of Products and Quotients
CHAPTER Continuity The Chain Rule. CHAPTER Continuity The Chain Rule If f and g are both differentiable and F = f o g is the composite function.
Trigonometry Review Find sin(  /4) = cos(  /4) = tan(  /4) = Find sin(  /4) = cos(  /4) = tan(  /4) = csc(  /4) = sec(  /4) = cot(  /4) = csc(
More On The Derivative Rules
Equation of a Tangent Line
Equations of Tangent Lines
Rate of change / Differentiation (3)
Find the slope of the tangent line to the graph of f at the point ( - 1, 10 ). f ( x ) = 6 - 4x
DIFFERENTIATION & INTEGRATION CHAPTER 4.  Differentiation is the process of finding the derivative of a function.  Derivative of INTRODUCTION TO DIFFERENTIATION.
Section 2.9 Linear Approximations and Differentials Math 1231: Single-Variable Calculus.
Derivatives - Equation of the Tangent Line Now that we can find the slope of the tangent line of a function at a given point, we need to find the equation.
Tic-Tac-Toe Using the Graphing Calculator for Derivatives.
Clicker Question 1 What is the derivative of f (x ) = e3x sin(4x ) ?
1.4 – Differentiation Using Limits of Difference Quotients
Differentiation Jeopardy Power RuleProduct RuleQuotient.
2.4 Chain Rule. Chain Rule If y=f(u) is a differentiable function of u and u=g(x) is a differentiable function of x then y=f(g(x)) is a differentiable.
Section 2.5 – Implicit Differentiation
How can one use the derivative to find the location of any horizontal tangent lines? How can one use the derivative to write an equation of a tangent line.
Implicit Differentiation
Chapter 4 Techniques of Differentiation Sections 4.1, 4.2, and 4.3.
2.3 The Product and Quotient Rules and Higher Order Derivatives
MAT 125 – Applied Calculus 3.2 – The Product and Quotient Rules.
Implicit Differentiation 3.6. Implicit Differentiation So far, all the equations and functions we looked at were all stated explicitly in terms of one.
Section 2.5 – Implicit Differentiation. Explicit Equations The functions that we have differentiated and handled so far can be described by expressing.
15. Implicit Differentiation Objectives: Refs: B&Z Learn some new techniques 2.Examples 3.An application.
Derivatives of Parametric Equations
Chapter3: Differentiation DERIVATIVES OF TRIGONOMETRIC FUNCTIONS: Chain Rule: Implicit diff. Derivative Product Rule Derivative Quotient RuleDerivative.
By: Jane Kim, Period 4, 2007 Source: Mr. Wiencek’s Noted from Class.
3.1 Definition of the Derivative & Graphing the Derivative
Definition of Derivative.  Definition   f‘(x): “f prime of x”  y‘ : “y prime” (what is a weakness of this notation?)  dy/dx : “dy dx” or, “the derivative.
Chapter 4 Additional Derivative Topics
Powerpoint Templates Page 1 Powerpoint Templates Review Calculus.
Some needed trig identities: Trig Derivatives Graph y 1 = sin x and y 2 = nderiv (sin x) What do you notice?
Chain Rule 3.5. Consider: These can all be thought of as composite functions F(g(x)) Derivatives of Composite functions are found using the chain rule.
Linear Approximation and Differentials Lesson 4.8.
Logarithmic Differentiation
Chapter 17.2 The Derivative. How do we use the derivative?? When graphing the derivative, you are graphing the slope of the original function.
3.5 – Implicit Differentiation
Math 1411 Chapter 2: Differentiation 2.3 Product and Quotient Rules and Higher-Order Derivatives.
Derivative Shortcuts -Power Rule -Product Rule -Quotient Rule -Chain Rule.
Rule 4 The chain rule 4/10/2013almuiz To illustrate 4/10/2013almuiz
After the test… No calculator 3. Given the function defined by for a) State whether the function is even or odd. Justify. b) Find f’(x) c) Write an equation.
DIFFERENCE QUOTIENT, DERIVATIVE RULES, AND TANGENT LINES RIZZI – CALC BC.
Unit 2 Lesson #1 Derivatives 1 Interpretations of the Derivative 1. As the slope of a tangent line to a curve. 2. As a rate of change. The (instantaneous)
§ 4.2 The Exponential Function e x.
Rules for Differentiation
Implicit Differentiation
(8.2) - The Derivative of the Natural Logarithmic Function
Used for composite functions
Find the equation of the tangent line for y = x2 + 6 at x = 3
MTH1170 Implicit Differentiation
Problem of the Day (Calculator Allowed)
Techniques of Differentiation
Linear Approximation and Differentials
2.4 The Chain Rule.
Implicit Differentiation
Part (a) Keep in mind that dy/dx is the SLOPE! We simply need to substitute x and y into the differential equation and represent each answer as a slope.
MATH 1314 Lesson 6: Derivatives.
The Chain Rule Section 3.4.
The Chain Rule Section 3.6b.
The Chain Rule Section 2.4.
More with Rules for Differentiation
Chapter 3 Additional Derivative Topics
Slope Intercept Form Algebra 1 Unit 4 Lesson 2.
Presentation transcript:

U2 L8 Chain and Quotient Rule CHAIN & QUOTIENT RULE UNIT 2 LESSON 8 CHAIN & QUOTIENT RULE

U2 L8 Chain and Quotient Rule Chain Rule and Quotient Rule Example 1 Find the derivative of 𝒚= 𝟏+𝟑𝒙 𝟒 𝟐 𝒙 𝟐 −𝟏 𝟐 dy = (2x2 – 1)2 [4(1 + 3x)3(3)] – (1 + 3x)4[2(2x2 – 1)(4x)] dx [(2x2 – 1)2]2 dy = (2x2 – 1)2 [12(1 + 3x)3] – (1 + 3x)4[8x(2x2 – 1)] dx (2x2 – 1)4

U2 L8 Chain and Quotient Rule Factor out common factors 4 , (2x2 – 1), and (1 + 3x)3 dy = (2x2 – 1)2 [12(1 + 3x)3] – (1 + 3x)4[8x(2x2 – 1)] dx (2x2 – 1)4 dy = 4 (2x2 – 1) (1 + 3x)3[3(2x2 – 1) – 2x(1 + 3x)] dx (2x2 – 1)4 dy = 4 (2x2 – 1) (1 + 3x)3[6x2 – 3 – 2x – 6x2] dx (2x2 – 1)4 dy = 4 (2x2 – 1) (1 + 3x)3(– 3 – 2x) dx (2x2 – 1)4 dy = 4 (1 + 3x)3(– 3 – 2x) dx (2x2 – 1)3

U2 L8 Chain and Quotient Rule Find the equation of the tangent line at x = 0. 𝒚= 𝟏+𝟑𝒙 𝟒 𝟐 𝒙 𝟐 −𝟏 𝟐 = 𝟏+𝟑(𝟎) 𝟒 𝟐 (𝟎) 𝟐 −𝟏 𝟐 =𝟏 Equation of tangent line 1 = 12(0) + b dy = 4 (1 + 3x)3(– 3 – 2x) dx (2x2 – 1)3 b = 1 dy = 4 (1 + 3(0))3(– 3 – 2(0)) dx (2(0)2 – 1)3 y = 12x + 1 Slope = dy = 4(1 )3(– 3) = 12 dx ( – 1)3

U2 L8 Chain and Quotient Rule Chain Rule and the Quotient Rule Example 2 U2 L8 Chain and Quotient Rule 𝒇 𝒙 = 𝟐𝒙+𝟏 𝒙 𝒇 𝒙 = 𝟐𝒙+𝟏 𝒙 𝟏 𝟐 Rewrite 𝑓 ′ 𝑥 = 1 2 times the parentheses to 1 2 –1 times the derivative of what's in the parentheses (quotient rule will be needed) 𝒇 ′ 𝒙 = 𝟏 𝟐 𝟐𝒙+𝟏 𝒙 − 𝟏 𝟐 𝒙 𝟐 −(𝟐𝒙+𝟏)(𝟏) 𝒙 𝟐 𝒇 ′ 𝒙 = 𝟏 𝟐 𝟐𝒙+𝟏 𝒙 − 𝟏 𝟐 𝟐𝒙−𝟐𝒙−𝟏 𝒙 𝟐 𝒇 ′ 𝒙 = 𝟏 𝟐 𝒙 𝟐𝒙+𝟏 𝟏 𝟐 −𝟏 𝒙 𝟐 𝒇 ′ 𝒙 = −𝟏 𝟐 𝒙 𝟐 𝒙 𝟐𝒙+𝟏